2019
DOI: 10.1002/cctc.201901268
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Nanoparticle Formation during Iridium‐Catalysed Oxygen Evolution by Real‐Time Small Angle X‐Ray Scattering

Abstract: Real‐time Small Angle X‐Ray Scattering (SAXS) has been used to investigate the homogeneity of a series of molecular iridium complexes during water oxidation catalysis in aqueous NaIO4 solution through a continuous flow cell. The results obtained for the unstable [Cp*Ir(OH2)3]2+ precursor forming amorphous IrOx nanoparticles (NPs) in‐situ validate and complement previous Dynamic Light Scattering (DLS) studies by providing enhanced sensitivity for small particle sizes and increased temporal resolution under real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Detection of in situ ‐generated nanoparticles can be very challenging. Hence, publications on molecular WOCs generally include multiple experiments to prove that the catalyst activity stems from a molecular species [44,52–54] . In the context of our ongoing research to explore novel first‐row metal‐based WOCs, [55] we were interested in developing novel nickel‐based catalysts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of in situ ‐generated nanoparticles can be very challenging. Hence, publications on molecular WOCs generally include multiple experiments to prove that the catalyst activity stems from a molecular species [44,52–54] . In the context of our ongoing research to explore novel first‐row metal‐based WOCs, [55] we were interested in developing novel nickel‐based catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, publications on molecular WOCs generally include multiple experiments to prove that the catalyst activity stems from a molecular species. [44,[52][53][54] In the context of our ongoing research to explore novel first-row metalbased WOCs, [55] we were interested in developing novel nickelbased catalysts. We aimed at applying previously developed design rules to optimize the catalyst, [56] but found that active NiO x layers are formed under certain conditions.…”
mentioning
confidence: 99%